Research on the Coordinated Development of Inclusive Finance and Public Services - Wu, Caitian; Xia, Yongxing; Chen, Hongxi (International Journal of Global Economics and Management, 2025)
Both inclusive finance and public service can provide services for the vast number of people. Although the two are different in the supply mechanism and the mode of government, they have the same service goal in different paths. By analyzing the theoretical mechanism of inclusive finance to promote the development of public service and the realization path of public service to promote the development of inclusive finance, this paper further introduces the research on the coordinated development of inclusive finance and public service, indicating that the business of the supply sector of the two can develop in tandem, and the coordinated development of the two is conducive to the integration of urban and rural development and the improvement of common prosperity.